The Effect of Climate Changes on The Fluctuation of The Water Level of Al- Razzaza Lake, Iraq - Al-Qaraghuli, Shahad A.; Hassan, Azhar A.; Albaldawi, Rafa A.; Abd, Omnia K. (Iraqi Journal of Science, 2021)
One of the serious environmental challenges that Iraq faces is climate changes and impacts of changing weather patterns and extreme global weather events. This paper addresses changes in the temporal and spatial characteristics of water levels of Razzaza Lake and response to climatic changes using archived series of Multispectral satellite images Landsat. TM, ETM+ and OLI images acquired on 1990, 2000 and of 2016. In order to extract, mapping the water surface area of the Razzaza Lake, Multispectral spectral band rationing the Normalized Difference Water Index (NDWI) technique was adopted, and the climatic elements data for the period (1990-2016) were analyzed which provide significant information of surface water. The results show that Razzaza Lake has a particularly sharp change rate in the water level and there are significant fluctuations on lake level and water surface area over the time.